Atrial fibrillation in retinal vascular occlusion disease and non-arteritic anterior ischemic optic neuropathy. - Josep Callizo; Nicolas Feltgen; Antje Ammermann; Janina Ganser; Sebastian Bemme; Thomas Bertelmann; Sebastian Pfeiffer; Andre Duvinage; Klaus Gröschel; Hans Hoerauf; Rolf Wachter (PLoS ONE, 2017)
Background Patients with retinal vascular occlusion disease have an increased risk for ischemic stroke and share some risk factors with cerebrovascular disease. The purpose of this study was to analyze the prevalence of atrial fibrillation (AF) in subjects with retinal vascular occlusive disease and anterior ischemic optic neuropathy and to compare these data to an ischemic stroke group. Methods Prospective, observational single-center trial. Subjects with retinal artery occlusion (RAO), retinal vein occlusion (RVO) and anterior ischemic optic neuropathy (AION) were included. Patients with ischemic stroke (IS) from a previous observational trial were used as control. Investigation included 7-day Holter ECG, echocardiography, duplex ultrasonography of the carotid arteries, and 24-hour blood pressure monitoring. Further vascular risk factors were documented. Results During the 1-year study period, 101 patients were recruited. The control group with ischemic stroke consisted of 272 subjects. At inclusion, the prevalence of AF was 12% (RAO), 10.2% (RVO), 11.1% (NAION) and 15.8% (IS). The final prevalence after Holter ECG rose to 16% (RAO), 18.4% (RVO), 14.8% (NAION) and 26.5% (IS). No significant difference was measured between groups. Conclusions We detected a similar prevalence of AF in all groups. RVO patients tended to exhibit a higher AF detection rate and lower number needed to screen than RAO and NAION. The detection of AF rose considerably via Holter ECG. As a consequence, we recommend prolonged ECG monitoring in patients with acute ophthalmic vascular diseases.